The Influence of Body Image towards Self-Esteem, SelfCompassion and Psychological Well-Being in Female Exerciser (Medico Legal Update, 2020)
Human development is a process of change that occurs throughout life. In adulthood, there are many changesin as such as cognitive, socio-emotional and physical changes. Body image is an individual experience in theform of perceptions of body shape and weight, as well as behaviours that lead to an individual’s evaluationof his physical appearance. Body image in women is very influential on their psychological factors such asself-esteem, self-compassion and psychological well-being. Sample of this research consisted of as many as100 female excersicer. The research was conducted in Lapangan Merdeka, Lapangan Cadika, and LapanganTeladan, Medan. Data were analysed by using simple logistic regression test and multiple logistic regression.The results of bivariate analysis found, the variables of self-esteem and self-compassion have an influenceon body image in female exercisers with the value p0.05, which means there is no relationship between self-esteem, self-compassion,and psychological well-being to body image. The results show that there is no relationship between selfesteem, self-compassion and psychological well-being to body image in female exerciser, these variablesdo not have a dominant influence meaning, all the three variables have the same influence on body image.Further findings show that self-esteem has a greater influence to body image on female exerciser.